Insight into phytase-producing microorganisms for phytate solubilization and soil sustainability - Rizwanuddin, Sheikh; Kumar, Vijay; Singh, Pallavi; Naik, Bindu; Mishra, Sadhna; Chauhan, Mansi; Saris, Per Erik Joakim; Verma, Ankit; Kumar, Vivek (Frontiers in Microbiology, 2023)
The increasing demand for food has increased dependence on chemical fertilizers that promote rapid growth and yield as well as produce toxicity and negatively affect nutritional value. Therefore, researchers are focusing on alternatives that are safe for consumption, non-toxic, cost-effective production process, high yielding, and require readily available substrates for mass production. The potential industrial applications of microbial enzymes have grown significantly and are still rising in the twenty-first century to fulfill the needs of a population that is expanding quickly and to deal with the depletion of natural resources. Due to the high demand for such enzymes, phytases have undergone extensive research to lower the amount of phytate in human food and animal feed. They constitute efficient enzymatic groups that can solubilize phytate and thus provide plants with an enriched environment. Phytases can be extracted from a variety of sources such as plants, animals, and microorganisms. Compared to plant and animal-based phytases, microbial phytases have been identified as competent, stable, and promising bioinoculants. Many reports suggest that microbial phytase can undergo mass production procedures with the use of readily available substrates. Phytases do not involve the use of any toxic chemicals during the extraction, nor do they release any such chemicals, thus they qualify as bioinoculants and supports soil sustainability. Besides, phytase genes are now inserted into new plants/crops to enhance transgenic plants reducing the need of supplemental inorganic phosphates and phosphate accumulation in the environment. The current review covers the significance of phytase in agriculture system, emphasizing its source, action mechanism, and vast applications.